2022
DOI: 10.3390/nu14153112
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of the Mediterranean Diet to Improve Mitochondrial Function in Experimental Models of Obesity and Metabolic Syndrome

Abstract: The abnormal expansion of body fat paves the way for several metabolic abnormalities including overweight, obesity, and diabetes, which ultimately cluster under the umbrella of metabolic syndrome (MetS). Patients with MetS are at an increased risk of cardiovascular disease, morbidity, and mortality. The coexistence of distinct metabolic abnormalities is associated with the release of pro-inflammatory adipocytokines, as components of low-to-medium grade systemic inflammation and increased oxidative stress. Adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 280 publications
0
16
0
Order By: Relevance
“…Potential therapeutic target via the myostatin and/or activin/follistatin axis [139]. Can occur alone or combined with O-MAFLD, requiring double therapeutic approach GAFLD Genetics-associated fatty liver disease Genetic variants either monogenic or polygenic not necessarily causing metabolic abnormalities [140 Yet-to-be-defined subgroups Conditions of FLD where etiology remains (temporarily or constantly) undefined (e.g., autoimmune hepatitis [143]; viral hepatitis [144]), or plays an emerging role (e.g., thyroid subclinical dysfunction [145], mitochondrial dysfunction [40,82,146,147] Fig. 3 Venn diagrams summarizing the current debate about the nomenclature of NAFLD in relation to other causes of fatty liver disease (FLD).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Potential therapeutic target via the myostatin and/or activin/follistatin axis [139]. Can occur alone or combined with O-MAFLD, requiring double therapeutic approach GAFLD Genetics-associated fatty liver disease Genetic variants either monogenic or polygenic not necessarily causing metabolic abnormalities [140 Yet-to-be-defined subgroups Conditions of FLD where etiology remains (temporarily or constantly) undefined (e.g., autoimmune hepatitis [143]; viral hepatitis [144]), or plays an emerging role (e.g., thyroid subclinical dysfunction [145], mitochondrial dysfunction [40,82,146,147] Fig. 3 Venn diagrams summarizing the current debate about the nomenclature of NAFLD in relation to other causes of fatty liver disease (FLD).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Notably, the recovery of the mitochondrial function with correct cholesterol trafficking could be a potential therapeutic strategy for IBD. In addition, it has been discussed that the high prevalence and incidence in industrialized countries could be related to a Western diet, due to the high intake of saturated fatty acids, cholesterol, refined carbohydrates, and sugar may impact the inflammatory status becoming essential during disease pathogenesis (189). Therefore, changing towards an increase in the intake of whole grains, vegetables, fruit, seeds, and polyunsaturated fatty acids, with are part of a Mediterranean diet characterized by a higher content of phytochemicals and essential fatty acids could bring benefits to IBD patients.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Conversely, Aleksandrova et al provides evidence that plant-based dietary patterns are associated with reduced levels of oxidative stress and inflammation and may be an effective method for the prevention of chronic diseases [ 127 ]. Concretely, polyphenols, plant-derived chemicals, and polyunsaturated fatty acids are just some of the MD ingredients that have been shown in several experimental settings to boost mitochondrial metabolism, biogenesis, and antioxidant capability ( Figure 2 ) [ 128 ]. Osorio-Conles et al also reported that a short-term MD intervention was associated with the elevated expression of genes involved in adipogenesis, angiogenesis, and autophagy [ 129 ].…”
Section: Diet and Inflammationmentioning
confidence: 99%